3D Resistivity Imaging Investigation for Engineering Construction Project Studies at Al-Muthana Airport in Baghdad, Iraq - Zghair, Murtadha M.; Al-Kubaisi, Manal Sh.; Karim, Hussein H. (Iraqi Journal of Science, 2023)
Engineering project assessment at Al-Muthana Airport in Baghdad, Iraq, has been studied using a 3D electrical resistivity imaging survey. The site investigation is crucial for assessing the future of the region’s infrastructures since it reveals the location of buried facilities or weak zones below the surface and measures localized groundwater levels. Wenner-Schlumberger array was used to conduct four parallel 2D electrical resistivity spreads (MU1 to MU4). Each spread line was 100 m in length with 1 m electrode spacing and an average spacing of 9 meters between any two adjacent lines. The depth of the investigation was around 23.8 m. Survey lines were drawn going from northwest to southeast. These spreads were combined to provide a 3D image of a 2700 m2 space.The robust inversion method and the inverse model generated using the standard least-squares method showed horizontal slices identified three zones with resistivity distribution ranging from 2 to 45.5 ohm.m. The first zone, from surface to 3.37 m, had relatively high resistivity of sandy silty clay soil with relatively low moisture content; the second zone, approximately from 3.37 to 12.2 m, had very low resistivity representing groundwater table; and the third zone, from 12.2 to 23.8 m representing high stiffness and density and relatively high resistivity due to gravel presence in the deposits. The second zone highlights potential risk zones for construction projects; as a result, it is advised that the zone surrounding the foundation be filled with a low permeability layer and that the towers be built on deep foundations.